Development and validation of an integrative scale to assess hope - Schrank, Beate (Health Expect, 2010)
Background  Hope includes the dimensions of time, goals, control, relations and personal characteristics. Existing tools that measure it vary in length and psychometric properties and cover different parts of its overall concept. Objectives  This study aimed to develop an instrument that integrates all relevant aspects of hope is concise, easy to use and shows good psychometric properties. Design  Three pre‐existing instruments (Miller Hope Scale, Herth Hope Index, Snyder Hope Scale) covering complementary and overlapping aspects of hope were administered cross‐sectionally to a general population sample (n = 489). Factor analysis was used for item reduction. Reliability and validity were tested using factor analysis and item correlations between the new scale and quality of life and depression scales. Setting and participants  The study was set in Austria. Participants were sampled from the general population using a quota sampling strategy. Results  The initial 60 items were reduced to a 23‐item scale with four dimensions: ‘trust and confidence’, ‘positive future orientation’, ‘social relations and personal value’ and ‘lack of perspective’. The new scale’s factor structure was highly stable and its internal consistency high (alpha = 0.92 for the overall scale, 0.80–0.85 for its subscales). Hope scores were negatively correlated with depression (r = −0.68) and positively with quality of life (r = 0.57), with the factor analysis and item discriminant validity supporting the new scale’s construct validity. Conclusions  The new scale comprehensively covers the concept of hope is significantly shorter than previous scales and shows satisfactory reliability and validity.